University scientism and American economic interests. Issue 3 (June 2018) - Langbert, Mitchell B.
This article outlines the evolution of the relationship between the emergence of large-scale finance and industry in the American Gilded Age and Progressive eras and the shaping and funding of universities by foundations linked to the emerging industries. Scientism has been a means of gaining and maintaining legitimacy and research funding. Statistics about recent donations reflect the earlier pattern, although the strongly elitist preferences of early funders and shapers of American higher education, such as the Carnegie Foundation for the Advancement of Teaching and the Rockefeller-Funded General Education Board, have moderated.